Mark an introduction and study guide : shaping the life and legacy of Jesus - Smith, Abraham 1957- (London, England Bloomsbury T & T Clark, 2020)
Introduction: Reshaping the memory of a teacher and his movement -- Mark as a life about Jesus -- Mark as a life for Jesus' followers -- Jesus as a prophetic envoy -- Jesus as a powerful broker -- Jesus as a philosophical hero.
This Guide reads the Gospel of Mark as a 1st-century CE story about Jesus, for his followers, and against tyranny or the abusive use of power. First, the book shows students how the Gospel uses the form of a traditional laudatory biography (a 'Life') to reshape the memory of the shame-ridden trials and suffering of Jesus. Such a biography portrayed Jesus' descent (as a son of God), his deeds, and his heroic death, dispelling any notion that the teacher Jesus was a charlatan or huckster. Second, Smith demonstrates how the Gospel devotes a great deal of space to Jesus' training of his disciples -- as he calls, commissions, and corrects them in preparation for the difficult moments of their journey. Third, Smith highlights the Gospel's special characterizations of Jesus - as a prophetic envoy, a man of authority, and a philosophical hero -- contrasting Jesus' use of power with the abusive use of power by Rome's representatives (Herod Antipas and Pilate)
Originally published in 2015 by Sheffield Phoenix Press
Includes bibliographical references and indexes
Also published in print.
Mode of access: World Wide Web.
Barrierefreier Inhalt: Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Keywords: Jesus Christ -- Biography; Bible -- Criticism, interpretation, etc; Biblical studies & exegesis; Electronic books